Effect of supplementary feeding of glucogenic and lipogenic diet on body parameters and onset of ovarian cyclicity in postpartum dairy buffaloes - GANIE, M A; PRABHAKAR, S; SINGH, A K; BRAR, P S (The Indian Journal of Animal Sciences, 2014)
The present study was undertaken to assess the effect of supplementation of glucogenic and lipogenic diets on certain physical parameters and onset of postpartum ovarian cyclicity in dairy buffaloes. Healthy postpartum pluriparous Murrah buffaloes (30) were classified into group 1, buffaloes (10) were supplemented with glucogenic precursor in addition to routine feeding; group 2, buffaloes (10) with rumen by-pass fat in addition to routine feeding; and group 3 buffaloes (10) maintained on routine diet without any additional supplementation served as control. The BCS was significantly high in group 2 buffaloes than in group 1 and group 3 buffaloes. Supplemented compared to control counterparts had significantly higher BW and BFT. The resumption of postpartum ovarian activity was influenced by nutrition. Group 2 and 1 buffaloes experienced early onset of first postpartum estrus than group 3 buffaloes. Thus, it can be recommended to supplement the diet with high energy rations in the early postpartum period to improve the reproductive efficiency of buffaloes.